LAG3 genotype of the donor and clinical outcome after allogeneic transplantation from HLA-identical sibling donors - Cruz, David; Rodríguez-Romanos, Rocío; González-Bartulos, Marta; García-Cadenas, Irene; de la Cámara, Rafael; Heras, Inmaculada; Buño, Ismael; Santos, Nazly; Lloveras, Natàlia; Velarde, Pilar; Tuset, Esperanza; Martínez, Carmen; et al. (Frontiers in Immunology, 2023)
The association of polymorphisms in molecules involved in the immune response (checkpoint inhibitors) with the clinical outcome after allogeneic transplantation (alloHSCT) has been described. Lymphocyte Activation 3 (LAG3) is a surface protein that plays a regulatory role in immunity as an inhibitory immune checkpoint molecule. To determine its role in the alloHSCT setting, we analyzed 797 patients transplanted from HLA-identical sibling donors. The LAG3 rs870849 C>T polymorphism was genotyped in donors. We detected a higher incidence of severe acute GVHD in patients transplanted from donors with TT genotype (p: 0.047, HR 1.64; 95% CI 1.01 – 2.67). Overall survival (OS) was worse for patients transplanted from donors with the rs870849 CT/TT genotype (0.020; HR, 1.44; 95% CI 1.06 – 1.96), as well as disease-free survival (DFS) (p: 0.002; HR 1.58, 95%CI: 1.18 – 2.14) and transplant-related mortality (TRM) (p< 0.001; HR: 1.88, 95% CI 1.29 – 2.74). When combining the LAG3 rs870849 and the PDCD1 rs36084323 genotypes of the donor, three genetic groups were well defined, allowing a good stratification of the risk of acute GVHD, TRM, OS and DFS. We conclude that the LAG3 genotype of the donor may be considered in donors’ selection. As this selection may be limited in the HLA-identical sibling donor scenario, further studies exploring the impact of LAG3 genotype of the donor in unrelated transplantation are warranted.